Mainstreaming Cash Waqf in Madrasah Curriculum: A Strategy for Integrating Islamic Philanthropic Literacy - Ferdinan Akrabi (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
The utilization of cash waqf as an instrument for sustainable madrasah education in Indonesia still faces significant obstacles, rooted in low literacy and understanding among the academic community. This condition is triggered by the lack of systematic integration of cash waqf material into the curriculum, as well as the lack of contextual teaching materials that can connect classical Islamic jurisprudence doctrine with modern social finance practices. This policy paper aims to formulate a strategy for mainstreaming cash waqf as a strategic issue in the madrasah education system to create financial independence for the institution. The policy methodology applied is a descriptive qualitative analysis through an Evidence-Based Policy Making (EBPM) approach, which includes a systematic literature review, a comparative analysis of regulations between Law Number 41 of 2004 concerning Waqf and national curriculum standards, and stakeholder mapping. The analysis shows that without a clear formulation of competencies in the domains of knowledge, attitudes, and practical skills, cash waqf will continue to be viewed as peripheral, supplementary material. The study recommends three key policy interventions: reorienting Graduate Competency Standards (SKL) to prioritize philanthropic literacy, developing digital modules based on investment instruments such as Cash Waqf Linked Sukuk (CWLS), and institutionalizing waqf management units as practical laboratories in madrasas. This integrated strategy is expected to transform madrasas from mere educational subjects into centers of an accountable Islamic philanthropic ecosystem, while equipping students with financial literacy relevant to future economic challenges.